Topics in Anti-Cancer Research: Volume 9 - Atta-ur-Rahman (Bentham Science Publishers, 2020)
Topics in Anti-Cancer Research covers new developments in the field of cancer diagnosis and drug therapy. Novel drugs as anticancer agents include natural and synthetic phenazirines and other anti-cancer compounds. The series also covers information on the current understanding of the pathology and molecular biology of specific neoplasms.The diversity of research topics published in this book series give broad and valuable perspectives for cancer researchers, clinicians, cancer professionals aiming to develop novel anti-cancer targets and patents for the treatment of various cancers.The topics covered in this volume are:- Recent Patents on Exosome-Derived Therapeutic Agents- Serrated Lesions of the Colon and Rectum: An Overview of Pathology and Emphasis on a New Classification- Introducing the 188W/188Re and 144Ce/144Pr Plaques for Eye Cancers Brachytherapy- ShcA Family of Adaptor Proteins: Dual Role in Cell Growth- Hormones Management as Anticancer Treatment and Protection: Functions and Mechanism of Action